O espaço-movimento do ciclista : seguindo o ciclista anônimo - Gabler, Luiz Gustavo (2017)
Nowadays urban mobilities stir political discourses and receive new attention from interdisciplinary studies, focused on the space of contemporary cities. Body movements, the human scale and the right to the city acquire importance due to the need to thin